All fours - July, Miranda 1974- (Riverhead Books, 2024)
"A semi-famous artist announces her plan to drive cross-country, from LA to NY. Twenty minutes after leaving her husband and child at home, she spontaneously exits the freeway, beds down in a nondescript motel, and immerses herself in a temporary reinvention that turns out to be the start of an entirely different journey"--
Keywords: Middle-aged women / Fiction; Artists / Fiction; Wives / Fiction; Automobile travel / Fiction; Motels / Fiction; Artists; Automobile travel; Middle-aged women; Motels; Wives; Voyages en automobile / Romans, nouvelles, etc; Femmes d'âge moyen / Romans, nouvelles, etc; Artistes / Romans, nouvelles, etc; Femmes mariées / Romans, nouvelles, etc; Motels / Romans, nouvelles, etc; Women artists / Fiction; Bisexual women / Fiction; Middle aged women / Fiction; Celebrities / Fiction; Man-woman relationship / Fiction; Hotels and motels / Fiction; Interior design / Fiction; California / Fiction; Fiction; Road fiction; Psychological fiction; Novels; Romans